Studi Retrospektif Penggunaan Antibiotik pada Pasien Covid-19 dengan Pneumonia di Rumah Sakit “X” Provinsi Bali, Indonesia - Siada, Nyoman Budiartha; Juanita, Rr Asih; Sanjaya, Dwi Arymbhi; Meriyani, Herleeyana (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2024)
COVID-19 with bacterial pneumonia co-infection is a condition with bacteria present in COVID-19 patients. The prevalence of bacterial co-infection in COVID-19 patients ranges from 12.4%–50%. This study aims to determine the relationship between the appropriate use of antibiotics and the severity of inpatients with COVID-19 and pneumonia co-infection at Hospital